Microbial Exopolysaccharides, Their Structures, Formation Mechanisms, and Effects on Human Health: Food-Related Microorganisms - Afranur Özçoban; Ayşe İlayda Boyacı; Hale İnci Öztürk (Turkish Journal of Agriculture: Food Science and Technology)
A biofilm is a complex matrix formed by microorganisms that includes exopolysaccharides, proteins, extracellular DNA, various enzymes, and the microorganisms themselves. Biofilm cell is a more stable form of microorganism than planktonic cell. Microbial cells attach themselves to the surface after certain signals or changes, colonize to create a more favorable environment for their growth and viability, and secrete exopolysaccharide. This component is the basic matrix of biofilm. The diversity of exopolysaccharides within biofilms varies significantly depending on their specific composition, contributing uniquely to the characteristics of biofilms. This diversity in biofilms underscores the need for targeted control strategies. Biofilms can be beneficial or harmful depending on the situation and where they develop. Accordingly, microbial biofilms have dual effects on health. Biofilms can have both harmful effects on health, such as contributing to antibiotic resistance and persistent infections, while biofilms formed by beneficial microorganisms play a crucial role in enhancing food functionality. Moreover, the formation of biofilm in certain foods can contribute to the enhancement of the product matrix, particularly by improving its texture. In this review, the structures of these biofilms, their basic components, their possible safety concerns, and health benefits are discussed. Moreover, this review deals with biofilm producing bacteria in foods and assesses the prevention strategies for biofilm formation within the food industry.